2014
DOI: 10.1007/s00440-014-0574-8
|View full text |Cite
|
Sign up to set email alerts
|

Information geometry and sufficient statistics

Abstract: Abstract. Information geometry provides a geometric approach to families of statistical models. The key geometric structures are the Fisher quadratic form and the Amari-Chentsov tensor. In statistics, the notion of sufficient statistic expresses the criterion for passing from one model to another without loss of information. This leads to the question how the geometric structures behave under such sufficient statistics. While this is well studied in the finite sample size case, in the infinite case, we encount… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
116
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(118 citation statements)
references
References 25 publications
2
116
0
Order By: Relevance
“…We obtain immediately from the Ay-Jost-Lê-Schwachhöfer theorem [4,Remark 3.23] and Theorem 1.2 the following Corollary 1.3. Let {Ω} be the class of topological spaces provided with Borel σ-algebra.…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…We obtain immediately from the Ay-Jost-Lê-Schwachhöfer theorem [4,Remark 3.23] and Theorem 1.2 the following Corollary 1.3. Let {Ω} be the class of topological spaces provided with Borel σ-algebra.…”
Section: Introductionmentioning
confidence: 82%
“…An indeterministic decision rule is a Markov transition distribution [11]. Recently, Ay-Jost-Lê-Schwachhöfer showed that a transformation between statistical models which is associated with a Markov transition distribution is a composition of the inverse of a transformation, which is associated with a sufficient statistic, and a transformation which is associated with a statistic [4,Theorem 4.10]. Hence, assuming the condition of invariance under sufficient statistics, the "information loss" condition is reduced to the case where data processing is associated with a statistic.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations